Impact of Sociodemographic and Dental Clinic Related Factors Causing Dental Anxiety in Patients: Factors Causing Dental Anxiety - Ullah, Asad; Khan, Amna Nauman; Khan, Nauman Rauf; Mirza, Waqas; Masood, Laiba; Mahreen, Aneesa (Pakistan Journal of Health Sciences, 2024)
Dental anxiety has been reported to be impacted by an individual’s sociodemographic characteristics like age, gender, marital status and level of education. This anxiety can be attributed to the pain experienced during dental treatment. Objective: To evaluate the impact of sociodemographic and dental clinic related factors causing dental anxiety in patients. Methods: A descriptive cross sectional study was conducted on 196 patients in Sharif Medical and Dental College, Lahore. Those with any psychological, systemic disorders and on medications were excluded. Participants who underwent dental extraction irrespective of their age, marital status, gender and education were included. Modified Norman Corah Dental Anxiety scale was used as data collection tool. Chi square was used to find the association between sociodemographic factors and dental anxiety level. Results: The study was done on 196 participants with 49% females and 51% males. Most of the patients (64.3%) were below 35 years of age while 35.7% were above it. Majority of the patients suffered severe dental anxiety (38%) followed by high (22%), moderate (20.9%) and mild (18.4%). Significant associations between gender and anxiety while taking dentist`s appointment (p=0.048), being next in turn at the clinic (p=0.029), being on the way to clinic (p=0.023) were seen. Significant impact of marital status on anxiety caused in patients going to the clinic was seen (p=0.039). Age also significantly affected dental anxiety in patients undergoing dental extraction (p=0.017). Conclusions: Severe dental anxiety was higher in the older age group. The impact of sociodemographic factors on dental anxiety due to dental clinic related factors (getting an appointment, waiting for their turn in clinic and on their way to the dentist) showed males and those who were married generally had a relaxed state of mind.